Analisis pengembangan produk kue bagea menggunakan metode quality function deployment (QFD) - Dhian Herdhiansyah; Andi Rini Wahyuni; Yusna Indarsyih; Asriani asriani; Sarinah Sarinah; Nur Asyik (AGROINTEK, 2025)
The aim of the research is to analyze the development of bagea cake products using the Quality Function Deployment (QFD) method. The research subjects were the parties involved in the micro business of bagea cake products, determining the number of samples using the Bernoulli formula. as many as 73. Determining the research location was carried out purposively. The analysis method used is Quality Function Deployment (QFD). The results of the research show that the development of bagea cake products using the QFD method shows that from 33 attributes, 6 attributes were obtained which were prioritized to be developed in accordance with consumer desires and needs with the highest value for each type of attribute, respectively: (1) taste attribute the bagea cake flavored product offered has its own characteristics with a value of 6.781 (3.00%), (2) the product texture attribute, namely bagea cake has a maturity standard that is in accordance with the food standards expected by consumers with a value of 6.863 (3.03%) , (3) product aroma attribute, namely the delicious and appetizing aroma of bagea cake with a value of 6.720 (2.97%), (4) product packaging design attribute, namely registered with BPOM (Food and Drug Supervisory Agency) with a value of 9.297 (3.43%), (5) product price attribute, namely the price of each bagea cake, is very suitable for the portion served with a value of 6.822 (3.26%) and (6) product quality attribute, namely the bagea cake product served has a distinctive characteristic with a value of 6.945 (3.07%). Technical requirements or technical responses for bagea cake products to meet consumer desires and needs start from providing raw materials, dough making process, dough forming process, baking process, cooling process, packaging process, inclusion of bagea cake product information on the packaging and attractive packaging design.